PML: a Language for Platform Modeling - Szemethy, Tivadar; Karsai, Gabor (Electronic Communications of the EASST, 2006)
Modeling the computational platforms is necessary to analyze the execution characteristics of systems developed using a model-based approach. In this paper, we introduce a novel platform modeling language: PML that is based on (a) transformational concepts borrowed from graph transformation languages, and (b) generative concepts from platform modeling, like ’kernel skeleton’. PML relies on higher-level, compact constructs that represent a special case of model transformations, and which are then used to specify platform semantics. The paper also illustrates how PML constructs can be compiled into lower-level constructs of more traditional model transformational languages, such as GReAT.